Strategy for strengthening brand association and perceived quality of private label products to increase repurchase intentions among indomaret consumers in palembang city - Oktavianti, Santi; Rahmania, Vanesha; Nurshanaya, Kaline Naena; Damayanti, Indri Dwi (Jurnal Mantik, 2025)
The growth of modern retail in Indonesia is driving increased competition, one of which is through the development of private label products. Indomaret, as one of the largest retail chains in Palembang, strives to increase its competitiveness by offering private label products. However, consumer doubts remain regarding the quality and brand associations of these products. This study aims to analyze the influence of brand associations and perceived quality on the repurchase intention of private label products among Indomaret consumers in Palembang City. This study used a quantitative approach with a survey method, where data were collected through questionnaires distributed to 384 respondents. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results showed that both brand associations and perceived quality had a positive and significant effect on the repurchase intention of private label products. This finding indicates that the stronger the brand association and the better the consumer's perception of product quality, the greater the likelihood of consumers making repeat purchases